Prevalence of High Serum Uric Acid Level in Patients with Chronic Kidney Disease Stage II-V - Acharya, Smriti; Sharma, Arun; Khadka, Sitaram; Bhandari, Gaurav; Thapa, Raj Kumar; KC, Kanchan; Acharya, Suyash (Journal of Karnali Academy of Health Sciences, 2022)
Background: Chronic kidney disease (CKD) has emerged as a significant public health issue affecting millions of individuals of all races and ethnic groups. It's also a major health burden in Nepal. Hyperuricemia is widely established as a risk factor for glomerulosclerosis, interstitial fibrosis, and atherosclerosis. However, reversing and preventing it in CKD will delay the course of chronic renal failure. Therefore, this research was designed to examine the uric acid profile in CKD patients who are receiving conservative therapy to avoid the worsening of CKD. Methods: The study included a total of 90 CKD patients at stages II-V. The complete history taking, clinical examination, and laboratory testing were done and the data were analyzed using SPSS version 22. The prevalence of hyperuricemia was determined and compared at various stages of CKD.Results: Among the enrolled patients (n = 90), the majority were male (66%) in gender. The maximum number of patients (44%) were elderly (60-80 years). Hyperuricemia was present in 80% of patients. Among them, two patients were in stage II (7.4±0.42), five in stage IIA (8.8±1.22), 25 in stage IIIB (8.59±1.63), 36 in stage IV (9.21±1.49), and three patients were in stage V (10.70±1.609).Conclusion: Serum uric acid levels were elevated in various stages of CKD patients. Thus, serum uric acid may be used as a predictive indicator of CKD. However, large-scale cohort research of the Nepalese population is suggested to corroborate the results of this study.